A Colorful Question Game to Improve Children Motor Skills in 4th Class Elementary School - Selvi Atesya Kesumawati; Aprizal Fikri; Noviria Sukmawati; Husni Fahritsani (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research aims to develop a basic motor skills learning model through game activities tailored to the developmental stages of students' ages. The game model used in this research is called "Colorful Question." This game is designed to enhance locomotor skills, particularly the basic movements of jumping and hopping, which are highly beneficial for training leg muscle strength, coordination, attention focus, and cognitive abilities of students. The research follows the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study are fourth-grade students in both boys' and girls' elementary schools, consisting of 27 participants in a small-scale pilot test and 65 participants in a large-scale pilot test. Validation results from experts show a CVI (Content Validation Index) value of 3.57 and a CVR (Content Validity Ratio) of 0.01, indicating that the developed "Colorful Question" game has high validity and is suitable for fourth-grade elementary school students, making it suitable for field testing (empirical validation).